Chitosan-based bionanocomposites for biomedical application - Kumari, Sangeeta; Singh, Raj Pal; Chavan, Nayaku N.; Annamalai, Pratheep K. (Bioinspired Biomimetic and Nanobiomaterials, 2018)
Natural polymers have greatly impacted the advancement of modern medicine. Natural polymer-based biomaterials are biodegradable. A significant advantage of natural polymers is that they can be broken down and removed from the body after they have served their function. A wide range of novel biomaterials from natural polymers has been investigated to meet new challenges in medical science. Chitosan is one of the natural polymers which have been widely used in the biomedical field. Nanotechnology is one of the most popular areas of current research. In the area of nanotechnology, polymer and metal/metal oxide nanoparticle matrix-based nanocomposites have generated a significant amount of attention in the recent literature. These bionanocomposites have wide-ranging applications in drug delivery and tissue engineering. This paper discusses polymer-metal/metal oxide nanoparticle matrix-based nanocomposite biomaterials and their applications in the biomedical field - that is, drug delivery and tissue engineering applications.